THE PATTERN OF CORRUPTION AN ERADICATION STRATEGY IN INDONESIA AS A DEMOCRATIC COUNTRY - Jiwa Muhamad Satria Nusantara (Asia Pacific Fraud Journal, 2019)
High rates of corruption in Indonesia be the one to proof that corruption is a comprehensive type of crime. Related to that, the pattern of corruption eradication must be comprehensive, simultaneous, holistic and integrated. In its development, the pattern of eradicating corruption in Indonesia needs to be done by "Systemic Thinking". So that existing patterns of corruption can be overcome, eradicated, and prevented from reaching the root. Eradicating corruption in Indonesia today still views corruption as partial and not patterned. Thus, the handling only focuses on the corruption case itself rather than the existing pattern of corruption. In principle, if we look at the pattern of corruption, society and bureaucratic factors is not one of the most fundamental aspects, it will begin with a political party factor that produces cadres of government leaders such as the president, governor, mayor, and legislator. This paper tries to illustrate how the democratic system correlates with patterns of corruption, what are the elements of weakness in the current democratic system in Indonesia which are the causes of corruption and how to solve it. There are four strategies that must be carried out to eradicate corruption in Indonesia, namely rearranging political parties, ethics and anti-corruption education for political party cadres, carrying out mandate of Article 15 of Law Number 2 of 1999 Concerning Political Parties related to financial reporting, and improving the audit cost of campaign costs.